Hepatitis C virus related cirrhosis decreased as indication to liver transplantation since the introduction of direct-acting antivirals: A single-center study - Ferrarese, Alberto (World J Gastroenterol, 2018)
AIM: To evaluate waiting list (WL) registration and liver transplantation (LT) rates in patients with hepatitis C virus (HCV)-related cirrhosis since the introduction of direct-acting antivirals (DAAs). METHODS: All adult patients with cirrhosis listed for LT at Padua University Hospital between 2006-2017 were retrospectively collected using a prospectively-updated database; patients with HCV-related cirrhosis were divided by indication for LT [dec-HCV vs HCV/ hepatocellular carcinoma (HCC)] and into two interval times (2006-2013 and 2014-2017) according to the introduction of DAAs. For each patient, indications to LT, severity of liver dysfunction and the outcome in the WL were assessed and compared between the two different time periods. For patients receiving DAA-based regimens, the achievement of viral eradication and the outcome were also evaluated. RESULTS: One thousand one hundred and ninty-four [male (M)/female (F): 925/269] patients were included. Considering the whole cohort, HCV-related cirrhosis was the main etiology at the time of WL registration (490/1194 patients, 41%). HCV-related cirrhosis significantly decreased as indication to WL registration after DAA introduction (from 43.3% in 2006-2013 to 37.2% in 2014-2017, P = 0.05), especially amongst dec-HCV (from 24.2% in 2006-2013 to 15.9% in 2014-2017, P = 0.007). Even HCV remained the most common indication to LT over time (289/666, 43.4%), there was a trend towards a decrease after DAAs introduction (from 46.3% in 2006-2013 to 39% in 2014-2017, P = 0.06). HCV patients (M/F: 43/11, mean age: 57.7 ± 8 years) who achieved viral eradication in the WL had better transplant-free survival (log-rank test P = 0.02) and delisting rate (P = 0.002) than untreated HCV patients. CONCLUSION: Introduction of DAAs significantly reduced WL registrations for HCV related cirrhosis, especially in the setting of decompensated cirrhosis.